Analysis of the South Slavic Scripts by Run-length Features of the Image Texture - Brodic, Darko; Milivojevic, Zoran N.; Amelio, Alessia (Elektronika ir Elektrotechnika, 2015)
The paper proposes an algorithm for the script recognition based on the texture characteristics. The image texture is achieved by coding each letter with the equivalent script type (number code) according to its position in the text line. Each code is transformed into equivalent grey level pixel creating an 1-D image. Then, the image texture is subject to the run-length analysis. This analysis extracts the run-length features, which are classified to make a distinction between the scripts under consideration. In the experiment, a custom oriented database is subject to the proposed algorithm. The database consists of some text documents written in Cyrillic, Latin and Glagolitic scripts. Furthermore, it is divided into training and test parts. The results of the experiment show that 3 out of 5 run-length features can be used for effective differentiation between the analysed South Slavic scripts. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12785